Structure, Process, and Outcomes of Liberian National Nursing and Midwifery Curricular Revisions. Issue 1 (8th October 2021) - Kpangaala-Flomo, Cecelia C.; Tiah, Mary W.; Zeantoe, G. Clinton; Loweal, Humphrey Gibbs; Matte, Rita Florence; Lake, Sodey C.; Altman, Susan D.; Mendoza, Maria; Tringali, Tanya; Stalonas, Kerry; Goldsamt, Lloyd; Kurz, Renata; et al.
Background: The Republic of Liberia has had major disruptions to the education of its health care cadres. Post Ebola, the Resilient and Responsive Health Systems (RRHS) initiative began a new era of capacity building with the support of PEPFAR and HRSA. Nursing and Midwifery serve as the largest healthcare cadres in Liberia. The national nursing and midwifery curricula were overdue for the regulated review and revisions. Methods: The Science of Improvement was used as the framework to accomplish this multilateral activity. The Institute for Healthcare Improvement's (IHI) stages of improvement included: 1) Forming the team, 2) Setting the aims, 3) Establishing measures, 4) Selecting measures, 5) Testing changes, 6) Implementing changes, and 7) Spreading changes. These stages served as the blueprint for the structures and processes put into place to accomplish this national activity. Findings: The RN, Bridging, and BScM curricula all had redundant content that did not reflect teaching pedagogy and health priorities in Liberia. Courses were eliminated or reconfigured and new courses were created. Development of Nursing and Midwifery Curricular Taskforces were not as successful as was hoped. Two large stakeholder meetings ensured that this was the curricula of the Liberian faculty, deans and directors, and clinical partners. Monitoring and evaluation tools have been adopted by the Liberian Board for Nursing and Midwifery to serve as another improvement to check that the new curricula are being implemented and to identify gaps that may require future cycles of change for continued quality and improvement. Conclusions: Developing trust among the multilateral partners was critical to the success of this activity. Networks have been expanded, and a proposed pilot with the Ghana Board of Nursing and Midwifery and the US academic partner will examine the feasibility of implementing electronic licensing examinations for nurses and midwives.